2003
DOI: 10.1124/dmd.31.8.1065
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Ginsenosides in Humans After Oral Administration

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Even though the degradation of ginsenosides has been thoroughly studied in animals and in vitro using acids, enzymes, and intestinal bacteria, knowledge concerning the systemic availability of ginsenosides and their degradation products in humans is generally lacking. Therefore, the attention in this article is focused on the identification of ginsenosides and their hydrolysis products reaching the systemic circulation in man. This is of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
330
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(336 citation statements)
references
References 20 publications
3
330
2
1
Order By: Relevance
“…13) Generally, deglycosylated ginsenosides are more easily absorbed by the human body and have more productive bioactive functions. 3,14,15) For example, ginsenosides Rg 3 , Rh 1 , Rh 2 and compound K are known to have excellent pharmacological effects. 14,16) Many people cannot fully benefit from the health effects of red ginseng due to limited ability to absorb ginsenosides.…”
mentioning
confidence: 99%
“…13) Generally, deglycosylated ginsenosides are more easily absorbed by the human body and have more productive bioactive functions. 3,14,15) For example, ginsenosides Rg 3 , Rh 1 , Rh 2 and compound K are known to have excellent pharmacological effects. 14,16) Many people cannot fully benefit from the health effects of red ginseng due to limited ability to absorb ginsenosides.…”
mentioning
confidence: 99%
“…major C.Y.WU et FENG) in human neuroblastoma SK-N-SH cells, and found that protopanaxadiol-type (ppd-type) saponins (ginsenoside Rb 1 , ginsenoside Rb 3 , notoginsenoside R 4 and notoginsenoside Fa) were the active compounds (Tohda et al, 2002). Ppd-type saponins are known to be completely metabolized into 20-O-b-D-glucopyranosyl-20(S)-protopanaxadiol (M1) by intestinal bacteria when taken orally (Odani et al, 1983;Tawab et al, 2003). Our previous report showed that M1 had axonal extension activity in degenerated neurons, and ameliorated memory disorder and synaptic loss in an Alzheimer's mouse model induced by (Tohda et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…MLB, a polyphenolic compound, is metabolized within a few hours after consumption [87] . In contrast, it takes a couple of days to metabolize the steroid-like ginsenosides in human body [88,89] . In light of our recent studies, we rationalize that the combinational usage of danshen and sanqi for the treatment of cardiovascular diseases takes the advantages of the non-toxic and yet strong Na + /K + -ATPase inhibitory potency of MLB to relieve the symptoms promptly and the moderate Na + /K + -ATPase inhibitory potency of ginsenosides to provide a relatively long-term basal therapeutic effect.…”
Section: Combinational Usage Of Danshen and Sanqi For The Treatment Omentioning
confidence: 99%
“…Nevertheless, ginsenosides might act as prodrugs, as they tend to be metabolized to their active forms by intestinal bacterial deglycosylation after oral administration [84] . Generally, the metabolites, easily absorbed by the intestines due to an increase of hydrophobicity after deglycosylation, might display the same or different pharmacological actions in comparison with their parent compounds [85] . Therefore, the cardiac therapeutic effects of ginseng and sanqi could very possibly be attributed to the effective inhibition of Na + /K + -ATPase by the metabolized ginsenosides, with sugar moieties attached only to the C-3 position of the steroid-like structure.…”
Section: Wwwchinapharcom Chen Rjy Et Almentioning
confidence: 99%